Forgiveness and Reconciliation in Palliative Care: The Gap between the Psychological and Moral Approaches - Leget, Carlo (Religions, 2020)
Forgiveness is an important theme in end-of-life care in all spiritual and religious traditions, although it is framed differently. Looking at research on forgiveness in palliative care literature from the last two decades, it is clear that forgiveness is predominantly carried out from a psychological perspective. According to this approach, forgiveness is seen as something that can be managed and taught in order to reduce stress and promote health. There is no doubt that this approach has its merits and is useful for dealing with guilt from the individual perspective of one’s own psychological health. From a moral perspective, however, forgiveness is more than dealing with personal feelings of guilt. In order to show the differences and gaps between the psychological and moral perspectives on forgiveness, I discuss the work of the German philosopher Svenja Flaßpöhler. I show that, from a moral perspective, forgiveness can neither be managed or taught, nor seen as a form of understanding, loving, or forgetting. As a conclusion, I formulate some recommendations for future research on forgiveness, distinguishing between the psychological and moral perspectives on forgiveness.